Moving Up the Social Ladder? Wages of First- and Second-Generation Immigrants from Developing Countries - Kevin Pineda-Hernández; François Rycx; Mélanie Volral (Global Labor Organization (GLO), 2022)
As immigrants born in developing countries and their descendants represent a growing share of the working-age population in the developed world, their labour market integration constitutes a key factor for fostering economic development and social cohesion. Using a granular, matched employer-employee database of 1.3 million observations between 1999 and 2016, our weighted multilevel log-linear regressions first indicate that in Belgium, the overall wage gap between workers born in developed countries and workers originating from developing countries remains substantial: it reaches 15.7% and 13.5% for first- and second-generation immigrants, respectively. However, controlling for a wide range of observables (e.g. age, tenure, education, type of contract, occupation, firm-level collective agreement, firm fixed effects), we find that, whereas first-generation immigrants born in developing countries still experience a sizeable adjusted wage gap (2.7%), there is no evidence of an adjusted wage gap for their second-generation peers. Moreover, our reweighted, recentered influence function Oaxaca-Blinder decompositions agree with these findings. Indeed, while the overall wage gap for first-generation immigrants born in developing countries is driven by unfavourable human capital, low-paying occupational/sectoral characteristics, and a wage structure effect (e.g. wage discrimination), the wage gap for their second-generation peers is essentially explained by the fact that they are younger and have less tenure than workers born in developed countries. Furthermore, our results emphasize the significant moderating role of geographical origin, gender, and position in the wage distribution.
Keywords: J15; J16; J21; J24; J31; J61; 330; Immigrants; intergenerational studies; labour market integration; wage decompositions; unconditional quantile regressions; employer-employee data